Environmental Software Systems. Infrastructures, Services and Applications 11th IFIP WG 5.11 International Symposium, ISESS 2015, Melbourne, VIC, Australia, March 25-27, 2015, Proceedings - Denzer, Ralf; Argent, Robert M.; Schimak, Gerald; Hřebíček, Jiří (IFIP Advances in Information and Communication Technology, 2015)
This book constitutes the refereed proceedings of the 11th IFIP WG 5.11 International Symposium on Environmental Software Systems, ISESS 2015, held in Melbourne, Australia, in March 2015. The 62 revised full papers presented were carefully reviewed and selected from 104 submissions. The papers are organized in the following topical sections: information systems, information modeling and semantics; decision support tools and systems; modelling and simulation systems; architectures, infrastructures, platforms and services; requirements, software engineering and software tools; analytics and visualization; and high-performance computing and big data.